Capacity solution for an elliptic coupled system with lower term in Orlicz spaces - AHAKKOUD, Yassine; BENNOUNA, Jaouad; EL MASSOUDI, Mhamed (Studia Universitatis Babeș-Bolyai Mathematica, 2025)
In this paper, we will deal with the capacity solution for a nonlinear elliptic coupled system with a Leray-Lions operator Au = −div σ(x, u, ∇u) acting from Orlicz-Sobolev spaces W10LM (Ω) into its dual, where M is an N -function. Mathematics Subject Classification (2010): 35J60, 35J66, 46E30. Received 09 April 2024; Accepted 01 March 2025.